Analysis of Arabic Language Learning at Karangsawo Paciran Lamongan Junior High School - Bangga, Taufik; Nafi, Ahmad Abu; Alkuzaini, Muhammad Na’im (Funun Arabiyyah: Journal of Arabic Education and Literature, 2025)
This study aims to analyze the Arabic language learning process at Karangsawo Pacira Lamongan Superior Junior High School, focusing on teaching methods, the role of teachers, learning media, and student learning motivation. Arabic as one of the important subjects in Islamic-based schools requires an effective learning approach in order to improve students' linguistic competence and understanding of Islam. This study uses a qualitative approach with observation, interview, and documentation methods to collect data from teachers, students, and learning documents. The results of the analysis show that Arabic language learning in this school has been carried out with various strategies, but there are still several obstacles such as the limitation of digital learning media and the lack of variety of teaching methods. In addition, student motivation tends to fluctuate depending on the teacher's approach to delivering the material. Therefore, innovation in learning methods and training for teachers is needed to improve the quality of Arabic language learning. This research is expected to be a reference for other schools in developing more effective and contextual Arabic language learning.